Persepsi Siswa Terhadap Perilaku Membolos di SMP Atthayyibah Kerinci - Afdha Lianti; Nuzmi Sasferi; Bukhari Ahmad (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
This research is motivated by the presence of students who are truant at SMP Atthayyibah Kerinci. This study aims to 1) Express student perceptions of acceptance at SMP Atthayyibah Kerinci, 2) Express student perceptions of understanding at SMP Atthayyibah Kerinci, 3) Express student perceptions in an assessment at SMP Atthayyibah Kerinci, 4) Reveal truancy behavior in school attendance at Atthayyibah Kerinci Middle School, 5) Expressing truancy behavior in class attendance at Atthayyibah Kerinci Middle School, 6) Expressing truancy behavior by doing homework at Atthayyibah Kerinci Junior High School, 7) Expressing truancy behavior in activities outside of school at Atthayyibah Kerinci Middle School. This type of research uses a descriptive method to determine the value of each variable, either one or more variables are independent without making any relationship or comparison with other variables. the number of samples in this study were 83 students, the sampling method used in this study was random (probability sampling). The results of this study were obtained that students' perceptions of acceptance were in the fairly good category 55 respondents with a percentage of 66%, students' perceptions of understanding were in a good enough category 48 respondents with a percentage of 58%, students' perceptions of assessment were in the fairly good category 38 people respondents with a percentage of 46%. Student truancy behavior in school attendance is in the good category 35 respondents with a percentage of 42%, Student truancy behavior in class attendance is in a good enough category 36 respondents with a percentage of 43%, Student truancy behavior by doing assignments is in a good category 26 respondents with a percentage of 31%, Student truancy behavior outside of school activities is in the good category 32 respondents with a percentage of 39%. Suggestion For further research who is interested in conducting research on student perceptions of truancy behavior, they can conduct research by adding research variables and other approaches so that the results obtained are better and more complete.